1985
DOI: 10.2737/fpl-gtr-43
|View full text |Cite
|
Sign up to set email alerts
|

Airborne sound transmission loss characteristics of woodframe construction

Abstract: Summary Table of ContentsThis report summarizes the available data on the airborne sound transmission loss properties of wood-frame construction and evaluates the methods for predicting the airborne sound transmission loss. The first part of the report comprises a summary of sound transmission loss data for wood-frame interior walls and floor-ceiling construction. Data bases describing the sound transmission loss characteristics of other building components, such as windows and doors, are discussed.The second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…The study found that the theory of Rudder (1985) produced no positive values. The theories of Leppington et al (1987) and Lee and Ih (2004) produced positive values at 100 to 160 Hz and 315 Hz.…”
Section: The En12354 Prediction Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…The study found that the theory of Rudder (1985) produced no positive values. The theories of Leppington et al (1987) and Lee and Ih (2004) produced positive values at 100 to 160 Hz and 315 Hz.…”
Section: The En12354 Prediction Methodsmentioning
confidence: 81%
“…It is a practical approximation to the particular integral of the bending wave partial differential equation of a single leaf homogeneous isotropic wall below the critical frequency which is more appropriate to use in this situation than Sewell's approximate correction factor (Sewell, 1970). It has no relationship to the particular integral at and above the critical frequency and is different from the approximation used by Sewell (1970), Rudder (1985), Leppington et al (1987), and Lee and Ih (2004) below the critical frequency. These authors use Sewell's (Sewell, 1970) approximate correction factor of…”
Section: The En12354 Prediction Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Solamente se han considerado referencias con mediciones en bandas de tercio de octava obtenidas mediante laboratorio según norma ISO 140-3 [23]- [26]. Los materiales utilizados con sus respectivas características físicas se muestran en la Tabla 1.…”
Section: Resultsunclassified
“…El objetivo de este trabajo de investigación es evaluar el modelo de predicción propuesto por los autores mediante una comparativa con el programa INSUL versión 9 y ensayos en condiciones de laboratorio disponibles en la bibliografía [23]- [26].…”
Section: Introductionunclassified